The efficacy of augmentative and alternative communication - Schlosser, Ralf W. (Augmentative and alternative communication perspectives series., 2003)
This book provides readers with essential tools for appraising evidence and outlining steps for planning and implementing better efficacy research. It aims to help researchers and practitioners develop the necessary skills for moving the augmentative and alternative communication field toward evidence-based practice. The Efficacy of Augmentative and Alternative Communication: Toward Evidence-Based Practice is a crucial addition to anyone's bookshelf who is involved in the AAC enterprise, including speech-language pathologists, special educators, physical therapists, occupational therapists, students in professional programs, individuals using AAC, their families, and applied researchers. It provides solutions to avoid common pitfalls of prominent research designs for evaluating efficacy and discusses how to formulate research questions and deal with issues of participant selection. It suggests how to plan and evaluate the integrity and social validity of interventions.